Beyond the Classroom Walls: Reconstructing Speaking Instruction through an Immersion-Based Culture in Nonformal Education - Rafael Ummar (Universitas Muhammadiyah Lampung, 2025)
This study aims to examine the reconstruction of speaking instruction through an immersion-based language culture in a nonformal English education context. A mixed-methods research design was employed by integrating quantitative frequency analysis and qualitative interpretive inquiry. Quantitative data were obtained by calculating the frequency and distribution of learning objectives, teaching techniques, instructional materials, and assessment practices observed during speaking instruction. Qualitative data were collected through classroom observations, semi-structured interviews, and document analysis to explore the pedagogical meanings underlying the quantitative patterns. The findings show that communicative objectives, interactive teaching techniques, contextualized materials, and formative assessment practices occurred most frequently and consistently across instructional sessions. Qualitative findings further reveal that the immersion-based culture extending beyond the classroom created authentic and sustained opportunities for speaking practice, which strengthened learners fluency, confidence, and willingness to communicate. The study concludes that effective speaking instruction in EFL contexts emerges from the systematic integration of pedagogical practices and immersion culture rather than isolated instructional techniques. Based on these results, it is recommended that English education programs incorporate immersion-oriented environments and data-informed formative assessment to support sustainable speaking development.